2020
DOI: 10.1073/pnas.1921791117
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic basis for microhomology identification and genome scarring by polymerase theta

Abstract: DNA polymerase theta mediates an end joining pathway (TMEJ) that repairs chromosome breaks. It requires resection of broken ends to generate long, 3′ single-stranded DNA tails, annealing of complementary sequence segments (microhomologies) in these tails, followed by microhomology-primed synthesis sufficient to resolve broken ends. The means by which microhomologies are identified is thus a critical step in this pathway, but is not understood. Here we show microhomologies are identified by a scanning mechanism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 38 publications
5
120
0
Order By: Relevance
“…In one study using mammalian cells, the efficiency of TMEJ was high when 2-4 bp microhomologies were directly adjacent to a DSB but dropped significantly when the distance from the break was increased to 10-30 bp. Increasing the length of microhomology to 6 bp rescued this distance-dependent decrease, illustrating that successful alt-EJ depends on a balance between the size of the microhomology and its location relative to the break [37,86].…”
Section: Microhomologymentioning
confidence: 90%
See 3 more Smart Citations
“…In one study using mammalian cells, the efficiency of TMEJ was high when 2-4 bp microhomologies were directly adjacent to a DSB but dropped significantly when the distance from the break was increased to 10-30 bp. Increasing the length of microhomology to 6 bp rescued this distance-dependent decrease, illustrating that successful alt-EJ depends on a balance between the size of the microhomology and its location relative to the break [37,86].…”
Section: Microhomologymentioning
confidence: 90%
“…Evidence from studies using mouse embryonic fibroblasts with Cas9-generated DSBs suggests pol theta can sample all microhomologous sequences for annealing within the 3 terminal 25 nucleotides of a pair of ends [10]. Iterative rounds of the annealing, synthesis, and dissociation steps can lead to insertions templated from regions around the DSB [20,32,37].…”
Section: The Mechanism Of Tmejmentioning
confidence: 99%
See 2 more Smart Citations
“…A dependence on polymerase theta for HR-deficient cells was noticed earlier in mouse embryonic fibroblasts 51 tumour cells: HR-deficient epithelial ovarian cancer cells depend on TMEJ 52 , whereas similar effects were recently observed for cisplatin-resistant lung cancer cells (which had upregulated polymerase theta expression) 53 . Moreover, it was recently shown that tumours with BRCA mutations show a significantly higher frequency of templated insertions, which is a hallmark of polymerase theta action, than BRCA proficient tumours 54 . The dependency of HR-deficient cancer cells on TMEJ point to polymerase theta as an interesting therapeutic strategy for a specific set of tumours.…”
Section: Discussionmentioning
confidence: 99%